Pemetaan Keterampilan Metakognitif dalam Pembelajaran Sains: Fungsi dan Tren Penelitian 2014-2023 - Hidayati, Sri (Balai Diklat Keagamaan Surabaya, 2024)
The development of metacognitive skills for learning has emerged as a major topic in educational research. This study aimed to: (1) map the function of metacognitive skills; and (2) identify study trends in metacognitive skills over the last ten years in science learning. Systematic Review of Literature (SLR) was used as the study methodology. Data were extracted from scientific publications published in leading international journals using the Scopus index and then uploaded to the Google Scholar and Scopus databases. The title and keywords